Dictionary of Authentic American Proverbs - Mieder, Wolfgang (Berghahn Books, 2021)
Dictionary of Authentic American Proverbs offers a comprehensive reference guide for distinctly American proverbs. Compiled by Wolfgang Mieder, a key figure in the field of proverb studies, this compendium features nearly 1,500 proverbs with American origins, spanning the 17th century to present day, including a scholarly introduction exploring the history of proverbs in America, the structure and variants of these proverbs, known authors and sources, and cultural values expressed in these proverbs. Along with a comprehensive bibliography of proverb collections and interpretive scholarship, this dictionary offers a glimpse into the history of American social and cultural attitudes through uniquely American language.